Adolescents' Interpersonal Negotiation Strategies: Does Competence Vary by Context?. (20th September 2020) - Baker, Elizabeth; Exner‐Cortens, Deinera
Abstract : Negotiating conflict in healthy ways is key to adolescents' social functioning. This paper examines interpersonal negotiation strategies (INS) (a developmental framework for navigating conflict) across three different contexts (friend, romantic, and parent) in a sample of 212 Canadian mid‐adolescents. Adolescents were asked how they would deal with a hypothetical conflict in each context. Adolescents were most advanced at negotiating conflict in the friend context, followed by parent and romantic contexts; negotiation skills were worst in the romantic context. Girls demonstrated a higher level of INS than boys, but only with friends. These results indicate the need for universal healthy relationship programs that support the development of conflict negotiation skills, especially within the new interpersonal context of romantic relationships.